Improved Anticancer Activity of the Malloapelta B-Nanoliposomal Complex against Lung Carcinoma - Thi Thao Do; Thi Nga Nguyen; Thi Phuong Do; Thi Cuc Nguyen; Ha Phuong Trieu; Phuong Thi Thu Vu; Tuan Anh Hoang Le (Applied Sciences, 2020)
Previous studies regarding malloapelta B (malB), a natural compound isolated from the Vietnamese medicinal plant, showed a strong NF-κB inhibitory effect, making it a promising source for the development of novel anticancer drugs. However, similar to many other natural compounds from plants, malB has several disadvantages for clinical applications, including high toxicity and low solubility. To improve its bioavailability, malB was conjugated into nanoliposomes, which are ideal drug carriers. The formulations with 1,2-dipalmitoyl-sn-glycero-3-phosphocholine, mPEG-cholesterol, malB, with or without cholesterol exhibited nanoliposomes with an average diameter of approximately 76.98 nm, PDI of 0.28, zeta potential of −5.53 mV, and the highest encapsulation efficiency of 78.73% ± 9.5%. These malB-nanoliposomes inhibited the survival of all lung cancer cell lines examined with IC50 values ranging from 11.86 to 13.12 µM. Moreover, malB-nanoliposomes showed stronger inhibition of A549 colony-forming activity compared to that of the free compound. The effects of malB and its nanoliposomal formulation may be mediated through activation of apoptosis by the significant induction of caspase 3 activity. The nanoliposomal formulations also showed potential to inhibit tumor growth (37.03%) and prolong survival (32.20 days) of tumor-bearing mice compared with the unloaded drug (p < 0.05). The improved antitumor activity of malB-nanoliposomes suggests their promising clinical applications.